The Concept of the Deming Cycle (PDCA) with the Administration in the Way of Buddhism - Suksongkram, Suksan (Journal of Thammawat, 2022)
In the period of the Educational Reform, one of the innovations in administration to be achieving the success, which has been recommended to utilize in the operation for accomplishing the goal with the great efficiency and effectiveness, is the quality cycle management process which is named Deming Cycle (typically known as the PDCA Cycle) proposed by Dr. W. Edward Deming. This quality cycle is a philosophical innovation, an elementary source of the intellect and the major science of the current administration cycle. There are generally hundreds of thousands of tools and methods for management. Nevertheless, all of them share an important core on the same basis of the Deming Cycle (PDCA). In this regard, the research study, the units of education as well as the students refer to the PDCA Cycle to be applied in the administration for the school or institution administrators.